2004
DOI: 10.1055/s-0038-1633409
|View full text |Cite
|
Sign up to set email alerts
|

Use of circular external skeletal fixator constructs to stabilize tarsometatarsal arthrodeses in three dogs

Abstract: SummaryThis report describes the use of circular external skeletal fixator (CESF) constructs for the stabilization of unilateral tarsometatarsal arthrodeses in three dogs with traumatic intertarsal or tarsometatarsal fracture/luxation injuries. The application of the CESF was performed following a limited approach to the intertarsal and tarsometatarsal joints. All three of the dogs developed post-operative wire tract inflammation with drainage and two dogs developed osteomyelitis. These complications resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[9][10][11] Implant failures include pin loosening, breakage or bending; clamp loosening; and connecting bar breakage. FAC rates in dogs of up to 100% have previously been reported; 8,12 more recent studies in cats have reported lower complication rates, ranging from 26-65%. 4,5,13,14 While individual studies have evaluated different ESF types at specific anatomical locations in defined groups of animals, it remains difficult to compare overall ESF complication rates.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…[9][10][11] Implant failures include pin loosening, breakage or bending; clamp loosening; and connecting bar breakage. FAC rates in dogs of up to 100% have previously been reported; 8,12 more recent studies in cats have reported lower complication rates, ranging from 26-65%. 4,5,13,14 While individual studies have evaluated different ESF types at specific anatomical locations in defined groups of animals, it remains difficult to compare overall ESF complication rates.…”
Section: Introductionmentioning
confidence: 92%
“…911 Implant failures include pin loosening, breakage or bending; clamp loosening; and connecting bar breakage. FAC rates in dogs of up to 100% have previously been reported; 8,12 more recent studies in cats have reported lower complication rates, ranging from 26–65%. 4,5,13,14…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been recommended that primary ligament repair should be accomplished as the treatment of choice whenever possible. Otherwise, prosthetic ligament reconstruction may mimic the ligament's action and ensure joint stability while allowing a suitable range of motion 2 , 10 , 18 , 36 . In this study, TESF was combined with primary ligament repair in 18 cats and with ligament prostheses in one cat.…”
Section: Discussionmentioning
confidence: 99%